2016
DOI: 10.1002/anie.201600234
|View full text |Cite
|
Sign up to set email alerts
|

Nanotexaphyrin: One‐Pot Synthesis of a Manganese Texaphyrin‐Phospholipid Nanoparticle for Magnetic Resonance Imaging

Abstract: The discovery and synthesis of novel multifunctional organic building blocks for nanoparticles is challenging. Texaphyrin macrocycles are capable and multifunctional chelators. However, they remain elusive as building blocks for nanoparticles because of the difficulty associated with synthesis of texaphyrin constructs capable of self-assembly. A novel manganese (Mn)-texaphyrin-phospholipid building block is described, along with its one-pot synthesis and self-assembly into a Mn-nanotexaphyrin. This nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In contrast, the porphysome is a recent example of a “one‐for‐all” approach in which the lipid nanoparticle is comprised of a single porphyrin‐lipid building block that when self‐assembled offers a multitude of intrinsic nanoscale functions . Previously developed porphyrin and porphyrin analog‐based lipids such as bacteriochlorophyll‐lipid and texaphyrin‐lipid have shown unique stimuli‐responsive properties and versatile metal‐chelation capabilities, respectively, for cancer imaging. We envision that it is possible for a non‐porphyrin‐based dye‐lipid building block, such as aza‐BODIPY, to assemble into a liposomal structure that introduces novel nanoscale optical properties and broadens the purview of “one‐for‐all” lipid nanoparticles.…”
Section: Figurementioning
confidence: 99%
“…In contrast, the porphysome is a recent example of a “one‐for‐all” approach in which the lipid nanoparticle is comprised of a single porphyrin‐lipid building block that when self‐assembled offers a multitude of intrinsic nanoscale functions . Previously developed porphyrin and porphyrin analog‐based lipids such as bacteriochlorophyll‐lipid and texaphyrin‐lipid have shown unique stimuli‐responsive properties and versatile metal‐chelation capabilities, respectively, for cancer imaging. We envision that it is possible for a non‐porphyrin‐based dye‐lipid building block, such as aza‐BODIPY, to assemble into a liposomal structure that introduces novel nanoscale optical properties and broadens the purview of “one‐for‐all” lipid nanoparticles.…”
Section: Figurementioning
confidence: 99%
“…As detailed below, we have found that MMn, 23 the manganese(II) analogue of MGd and MLu, provides an effective PA imaging agent with greater photostability than ICG. MMn is also appealing in that it has demonstrated MRI enhancing capabilities 24,25 and is expected to be free of the toxicity concerns associated with certain gadolinium-based imaging agents (e.g., Magnevist). 26−28 For the present PAI-based experiments, each compound was dissolved in doubly distilled water and then each solution was placed into a 1.1 mm diameter plastic tube and subjected to a laser fluence of 5 mJ/cm 2 .…”
mentioning
confidence: 99%
“…As detailed below, we have found that MMn , the manganese­(II) analogue of MGd and MLu , provides an effective PA imaging agent with greater photostability than ICG . MMn is also appealing in that it has demonstrated MRI enhancing capabilities , and is expected to be free of the toxicity concerns associated with certain gadolinium-based imaging agents (e.g., Magnevist). …”
mentioning
confidence: 99%
“…[1,2] However,e fforts to transform the liposome from asingular drug delivery vehicle into am ultimodal theranostics nanoplatform have centered around an "all-in-one" approach, wherein different functional moieties are combined for multifunctional utility.T his inherent complexity led to significant challenges in their clinical translation. [4] Previously developed porphyrin and porphyrin analog-based lipids such as bacteriochlorophylllipid [5,6] and texaphyrin-lipid [7,8] have shown unique stimuliresponsive properties and versatile metal-chelation capabilities,r espectively,f or cancer imaging.W ee nvision that it is possible for an on-porphyrin-based dye-lipid building block, such as aza-BODIPY,t oassemble into aliposomal structure that introduces novel nanoscale optical properties and broadens the purview of "one-for-all" lipid nanoparticles. [4] Previously developed porphyrin and porphyrin analog-based lipids such as bacteriochlorophylllipid [5,6] and texaphyrin-lipid [7,8] have shown unique stimuliresponsive properties and versatile metal-chelation capabilities,r espectively,f or cancer imaging.W ee nvision that it is possible for an on-porphyrin-based dye-lipid building block, such as aza-BODIPY,t oassemble into aliposomal structure that introduces novel nanoscale optical properties and broadens the purview of "one-for-all" lipid nanoparticles.…”
mentioning
confidence: 99%
“…[3] In contrast, the porphysome is ar ecent example of a" one-for-all" approach in which the lipid nanoparticle is comprised of asingle porphyrin-lipid building block that when self-assembled offers amultitude of intrinsic nanoscale functions. [4] Previously developed porphyrin and porphyrin analog-based lipids such as bacteriochlorophylllipid [5,6] and texaphyrin-lipid [7,8] have shown unique stimuliresponsive properties and versatile metal-chelation capabilities,r espectively,f or cancer imaging.W ee nvision that it is possible for an on-porphyrin-based dye-lipid building block, such as aza-BODIPY,t oassemble into aliposomal structure that introduces novel nanoscale optical properties and broadens the purview of "one-for-all" lipid nanoparticles.…”
mentioning
confidence: 99%